2016
DOI: 10.1186/s13054-016-1441-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of prokinetic agents in critically ill patients receiving enteral nutrition: a systematic review and meta-analysis of randomized trials

Abstract: BackgroundIntolerance to enteral nutrition is common in critically ill adults, and may result in significant morbidity including ileus, abdominal distension, vomiting and potential aspiration events. Prokinetic agents are prescribed to improve gastric emptying. However, the efficacy and safety of these agents in critically ill patients is not well-defined. Therefore, we conducted a systematic review and meta-analysis to determine the efficacy and safety of prokinetic agents in critically ill patients.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 59 publications
6
99
0
6
Order By: Relevance
“…There was no significant effect on the risk of pneumonia or vomiting. The majority of trials examined the effect of metoclopramide or erythromycin; subgroup analysis by drug class was underpowered to detect important subgroup differences [606]. We considered the desirable consequences (lower risk of feeding intolerance) and the low quality of evidence showing no difference in mortality or pneumonia, and issued a weak recommendation for using prokinetic agents (metoclopramide or erythromycin) to treat feeding intolerance in patients with sepsis.…”
mentioning
confidence: 99%
“…There was no significant effect on the risk of pneumonia or vomiting. The majority of trials examined the effect of metoclopramide or erythromycin; subgroup analysis by drug class was underpowered to detect important subgroup differences [606]. We considered the desirable consequences (lower risk of feeding intolerance) and the low quality of evidence showing no difference in mortality or pneumonia, and issued a weak recommendation for using prokinetic agents (metoclopramide or erythromycin) to treat feeding intolerance in patients with sepsis.…”
mentioning
confidence: 99%
“…Intestinal dysfunction can be suspected in cases of diarrhea, vomiting, bloating, abdominal pain, and/or digestive bleeding . Prokinetic drugs may improve gastroparesis and enable early nutrition . Diarrhea should be promptly investigated and managed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that MMCs presented a dose-dependent response to erythromycin in humans [12, 25], and the dose of erythromycin varied greatly in different post-pyloric placement trials [26, 27]. Thus, 2 g of erythromycin was ultimately chosen on the basis of the dose-dependent property and reference to the drug instruction, although higher doses are available and usually adopted to control Legionella infection.…”
Section: Discussionmentioning
confidence: 99%